The willingness to voluntarily apply international financial reporting standards in Vietnam: Empirical evidence from listed parent companies - Thu Hien Nguyen (Cogent Business & Management, 2022)
In the current period of increased globalization, the preparation and presentation of financial statements by international financial reporting standards (IFRS) are receiving support from many countries and territories around the world, as applying IFRS is a way for them to gain acceptance in the international business world. To converge global accounting standards and promote regional and global economic integration, Vietnam has announced a roadmap for the voluntary application of IFRS from 2022 for some listed parent companies and others having needs and sufficient resources. This study aims to examine some specific characteristics of Vietnamese listed parent companies that affect their willingness to apply IFRS voluntarily. This study uses descriptive statistics, univariate, and multivariable regression methods to analyze the data collected from audited consolidated reports in the 2020 fiscal year and surveys the managers of 400 Vietnamese listed parent companies. Empirical research results confirm that several specific characteristics such as firm size, profitability, type of auditors, and foreign investors influence the voluntary application of IFRS of listed parent companies. In the meantime, other factors such as leverage and foreign operations do not affect the voluntary application of this accounting standard.
Keywords: 650; enterprises; IFRS; listed parent companies; voluntarily apply